(untitled) (Ius Novum, 2021)
The article concerns the possibility of applying general directives of imposition of penalty (including general crime prevention) in the case of granting a sentenced person conditional release from deprivation of liberty. According to one of the views, Article 77 § 1 of the Penal Code sets out the grounds for conditional release an enumerative manner, which prevents the application of Articles 53–55 of the Penal Code. According to the opposition’s view, Article 56 of the Penal Code orders also to take into account the general directives of imposition of penalty. The Supreme Court in its resolution of 26 April 2017, I KZP 2/17, supported the first concept. The author of the text gives a number of arguments for adopting the opposite view. As far as Article 77 § 1 puts emphasis only on achieving the resocialization goal, Article 56 also orders the use of general directives of imposition of penalty. Although the granting of conditional release does not constitute a imposition of penalty, it modifies the effects of a penalty decision, so it should respect the objectives, principles and directives of the penalty. The legislator in Article 77 § 2 allowed the court in jurisdiction proceedings to tighten the conditions for using the releasing. The court makes a decision in this case only on the basis of Articles 53–55. He cannot do it pursuant to the Article 77 § 1, because the perpetrator did not even start the penalty.